Measuring decentering as a unidimensional construct: The development and initial validation of the Decentering Scale for Sport. (May 2016) - Zhang, Chun-Qing; Chung, Pak-Kwong; Si, Gangyan; Gucciardi, Daniel F.
Abstract: Decentering, the ability to observe one's thoughts and feelings from a detached view, has gained increased attention in recent years. With this renewed interest comes a need for a reliable and valid tool to measure decentering in sport contexts. Therefore, in this multi-study paper we report the development and initial validation of a sport-specific self-report measure of decentering, the Decentering Scale for Sport (DSS). Based on an initial pool of context-specific items with acceptable content validity, a unidimensional decentering construct was confirmed in four independent athletic samples ( n  = 1255). Satisfactory internal consistency reliability and partial measurement invariance across gender and sport type was demonstrated. Convergent and concurrent validity of the DSS was established by showing positive and medium to large associations with mindfulness, well-being, flow, vitality, enjoyment and positive affect, and negative and medium to large associations with cognitive fusion, experiential avoidance, anxiety and negative affect. Discriminant validity of decentering with mindfulness and self-compassion was also established. Findings suggest that the DSS is a reliable and valid measure of decentering in sport contexts, and can be applied in future research and applied practice to measure decentering. Highlights: We developed and offered initial validity evidence for a unidimensional self-report instrument to measure decentering in sport contexts. Satisfactory internal consistency reliability, convergent, concurrent, and discriminant validities, and partial measurement invariance across gender and sport type were demonstrated in four independent samples of Chinese athletes. The importance of synthesizing and differentiating the construct of decentering with similar concepts (e.g., cognitive defusion and re-perceiving) is highlighted.